PROHIBITIONS IN FINANCIAL LAW: THE CONCEPT, TYPES AND FORMS OF IMPLEMENTATION - Dmitrij Smirnov; Leila Botasheva (Гуманитарные и юридические исследования)
It is generally recognized that financial law is one of the most complex public sectors of law, developed at the intersection of economics and law. An important vector in the development of our state is the formation of a digital economy that requires the creation of new innovative financial instruments, which in fact determines the need for the development of new legislative approaches in the regulation of financial relations. The role of financial law is difficult to overestimate. Modern financial law is represented by a set of rules designed to protect mainly values related to public interests. The financial law is characterized by an imperative-dispositive method of legal regulation, the prevalence of orders and prohibitions, not the permissions. The article is devoted to the analysis of the role of prohibitions in financial law. The issues of the legal nature of financial and legal norms are examined in detail. The article analyzes the peculiarities of the implementation of prohibitive norms of financial law, there is a tendency of the predominance of positive binding and prohibitions in financial and legal regulation based on the imperativeness of legal regulation methods. The authors specify classification of prohibitions in financial law, their conditional character is noted. It is noted that the norms of legislation should also take into account private and public interests, since the development and state of the entire financial system of the state depends on the balance of prohibitions and permissions in financial law.